Intra- and Inter-industry Externalities from Foreign Direct Investment in the Mexican Manufacturing Sector: New Evidence from Mexican Regions - Jordaan, Jacob A. (World development, 2008)
This paper presents new empirical evidence on externalities from Foreign Direct Investment (FDI) in several Mexican regions in the early 1990s. The main findings are threefold. First, the presence of FDI creates negative externalities within industries and positive externalities between industries through backward linkages. Second, FDI-externalities are stimulated by large technological differences between FDI and Mexican firms and by geographic concentration of industries. Third, we identify a substantial level of regional heterogeneity of the externality impact of FDI, in line with the notion that FDI may have contributed to processes of changing regional prosperity under trade liberalization. The findings also imply that maquiladora firms in the border states are generating positive externalities.